Radiopharmaceutical Fractionation as a Crisis Management Strategy: Experience with 99mTc-DTPA - Islam, Sanjida; Islam, Md Ariful; Biswasarma, Sanchoy Chandra; Khatun, Afifa; Azim, Mohammad Anwar Ul; Islam, Md Saiful; Banu, Most Layla Saroware (Bangladesh Journal of Nuclear Medicine, 2026)
Imaging with ⁹⁹ᵐTc-DTPA is a standard technique for assessing renal function. A single vial of DTPA cold kit contains sufficient amount of ligand for multiple dose preparation. This study was conducted to optimize kit utilization during a nationwide supply shortage by adapting kit fractionation approach. In this study a full vial of DTPA kit was aseptically divided into three aliquots using 0.9% and preserved at 4°C. Then the fraction was used over multiple days, with each fraction radiolabeled using freshly eluted ⁹⁹ᵐTc. Radiochemical purity (RCP) was assessed by ITLC-SG and consistently remained ≥ 95% in all fractions. The average of % RCP of DTPA fractions 96.77%. All clinical studies produced satisfactory image quality without the need for repeat imaging. This approach of kit fractionation led to reduced kit consumption, minimized waste, and improved operational efficiency. Additionally, this method can be considered as annual cost reduction method. Bangladesh J. Nuclear Med. 28(2): 247-250, July 2025